The influence of natural wind patterns on the thermal and humidity comfort of the “one seal” building in Yunnan, China - Zhenghong Yang; Keqiang Liao; Wei Jiang; Yaoning Yang; Jie Zhou (Journal of Asian Architecture and Building Engineering)
The thermal and humidity environments of buildings under the influence of the Heating, Ventilation and Air Conditioning (HVAC) systems constitute a mature topic in the field of architecture, but there are few studies on the thermal and humidity environments of traditional rural buildings under natural wind conditions. In this paper, a traditional one-seal residential building in Kunming, Yunnan Province, was adopted as the research object. By arranging monitoring instruments, we collected thermal and humidity environment and natural wind data of the building under three weather conditions: cloudy, sunny and rainy days. The results showed that climate change can alter the thermal and humidity stability levels of the building, and there are differences in thermal and humidity stability among the different spatial structures inside the building. Natural wind plays a significant role in reducing the humidity of the environment and building surfaces, and the thermal and humidity properties of the building materials play an important role in maintaining the thermal and humidity stability levels of the building. The results of this study provide a basis for obtaining a greater understanding of heat and humidity comfort levels in naturally ventilated areas and thermal and humidity environments of traditional buildings at the later stage.